(untitled) (Docentes 2.0 Journal, 2024)
Rapid advances in the scientific and technological fields, especially in information and communication technologies (ICT), demand an educational model that stimulates innovative thinking in students. The study’s primary objective was to propose an innovative educational strategy integrating gamification, digital literacy, and technology to enhance mathematics teaching to fourth-grade students in Bogotá, Colombia. It was situated in the holistic paradigm, holographic method, experimental approach, descriptive, propositional, transectional design, and projective type, based on measurements of variables to establish characteristics that affect a problem, requiring the validation of instruments. The diagnosis results show a low level of mathematical competencies attributed to cognitive and methodological deficiencies in 135 students from 3 district educational institutions in Bogotá, D.C. In the end, this pedagogical approach becomes a technological tool that enhances the dynamics of teaching and learning. The study is based on a teaching strategy that integrates technology, gamification, and the teaching of mathematical concepts, seeking to enhance students’ interest and active participation in learning this discipline.